Emotional experience as a target of psychotherapeutic impact - Лисеная, А. М. (Psychological Counseling and Psychotherapy, 2018)
This article deals with different psychological approaches in the investigation of the emotional experience as an element of the emotional life of the person. Review of the basic material is devoted to the study of the psychotherapeutic emotional experience context, and structural characteristics of the emotional experience, as they both are of the essential significance for the psychotherapeutic process.